Morse family papers - Morse, Charles Nathan, 1837-1880
Letter (1852) to Isaac Edward Morse, U.S. representative from Louisiana, suggesting that he run for governor of Louisiana, and autograph collection, probably collected by Morse; letter (1832) to Nathan Morse, recorder for the city of New Orleans, La., notifying him of his reelection to that post; correspondence (1806-1810) of P.C. Wederstrandt relating primarily to his activities as a naval officer; correspondence and orders to duty (1854-1864) of Charles Nathan Morse, Confederate Army officer; correspondence (1835) between William Moore, U.S. Army officer, and his wife, Chess; 9 letters of the Marquis de Lafayette, l letter each from Charles Carroll of Carrollton, Sam Houston, Andrew Jackson, and Martin Van Buren; and miscellaneous biographical material.
In part, negative photocopies.
Collection material in English.
Keywords: Carroll, Charles, -- 1737-1832 -- Correspondence; Houston, Sam, -- 1793-1863 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834.; Moore, Chess -- Correspondence; Moore, William -- Correspondence; Morse, Isaac Edward, -- 1809-1856 -- Correspondence; Morse, Nathan, -- 1784-1833 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Wederstrandt, P. C., -- 1776-1835? -- Correspondence; Morse family; Louisiana -- Politics and government -- 1803-1865.; Autographs -- Collections; Army officers, Confederate; Naval officers; Representatives, U.S. Congress -- Louisiana